Exogenous Cry1Ab/c Protein Recruits Different Endogenous Proteins for Its Function in Plant Growth and Development - Fu, Jianmei; Liu, Biao (Frontiers in Bioengineering and Biotechnology, 2020)
Current risk assessments of transgenic crops do not take into consideration whether exogenous proteins interact with endogenous proteins and thereby induce unintended effects in the crops. Therefore, the unintended effects through protein interactions in insect-resistant transgenic rice merit investigation. Here, a yeast two-hybrid assay was used to evaluate interactions between Bacillus thuringiensis (Bt) protein-derived Cry1Ab/c insect resistance rice Huahui-1 and the endogenous proteins of its parental rice Minghui-63. The authenticity of the strongest interactions of Cry1Ab/c and 14 endogenous proteins involved in photosynthesis and stress resistance, which may be primarily responsible for the significant phenotypic differences between transgenic Huahui-1 and parental Minghui-63, were then analyzed and validated by subcellular co-localization, bimolecular fluorescence complementation and co-immunoprecipitation. As the exogenous full-length Cry1Ab/c protein was found to have self-activating activity, we cleaved it - into three segments based on its three domains, and these were screened for interaction with host proteins using the yeast two-hybrid assay. Sixty endogenous proteins related to the regulation of photosynthesis, stress tolerance, and substance metabolism were found to interact with the Cry1Ab/c protein. The results of bimolecular fluorescence complementation and co-immunoprecipitation verified the interactions between the full-length Cry1Ab/c protein and 12 endogenous proteins involved in photosynthesis 23KD, G, PSBP, Rubisco, Trx, THF1 and stress resistance CAMTAs, DAHP, E3s, HKMTs, KIN13A, FREE1. We used a combination of yeast two-hybrid, bimolecular fluorescence complementation, and co-immunoprecipitation to identify Cry1Ab/c interacting with rice proteins that seem to be associated with the observed unintended effects on photosynthesis and stress resistance between Huahui-1 and Minghui-63 rice plants, and analyze the possible interaction mechanisms by comparing differences in cell localization and interaction sites between these interactions. The results herein provide a molecular analytical system to qualify and quantify the interactions between exogenous proteins and the endogenous proteins of the recipient crop. It could help elucidate both the positive and negative effects of creating transgenic plants and predict their potential risks as well as net crop quality and yield.